The excavation of an 18th-century pottery at Gallowgate, Glasgow. Issue 1 (March 2015) - Paton, Kevin
Abstract : The excavations at 239 Gallowgate, Glasgow revealed elements of an 18 th century pottery works known as the 'Pighouse'. As well as the corner of the potter's house and workshop, several sections of the flue system, a chimney base and a possible drying shed were revealed, providing indications of the later pottery tenement layout and allowing interpretations to be made about the location of the 'Pighouse' kiln. Furthermore, finds from several waster pits located around the pottery structures give some indication of the ceramics being produced. Finally, remnants of other small industries occupying the site during the late 18th century were revealed that provide an indication of the industrial nature of Glasgow's east end.